NEED FOR NOTIFYING AND PREVENTION OF CONGENITAL ANOMALIES: Congenital Anomalies - Mahmud, Shahid; Ali Shah, Sajid (Pakistan Armed Forces Medical Journal, 2017)
Objective: To determine the frequency of different systems involved in congenital anomalies to prevention and notifying strategies. Study Design: Descriptive observational study. Place and Duration of Study: The study was carried out at Military Hospital, Rawalpindi, from Jan 2011 to Aug 2013. Material and Methods: The study was carried out at Military Hospital, Rawalpindi. The data of all the neonates with congenital anomalies was analyzed in term of sex and various system involved. Various type of tests were used for the diagnosis of different defects like, barium studies, computed topography, magnetic resonance imaging, echocardiography, x-rays, ultrasound. Results: Total number of admissions during the study period were 4201 out of which 371 (8.83%) were diagnosed cases of congenital anomalies. Of these babies 220 (59.30%) were male, 142 (38.27%) were females and the remaining 9 (2.43%) were with ambiguous genitalia 215 (57.95%) were delivered by normal vaginal delivery and rest 156 (42.05%) by lower segment caesarian section. The most common system involved was central nervous system (CNS) 89 (23.99%), followed by gastro intestinal tract 74 (19.95%), cardiovascular system 61 (16.44%), respiratory system 35 (9.43%) and genito urinary system 18 (4.85%). Babies with dysmorphic features were 48 (12.94%) and with cleft lip and palate 17 (4.58%). The remaining 29 (7.82%) were grouped in miscellaneous category. Conclusion: Congenital anomalies are an important cause of admission to NICU. The prevalence of congenital anomalies was found more in males than in females. In our set up the most common system involved in congenital anomalies is central nervous system followed by gastrointestinal tract and cardiovascular systems